Pengaruh Kompetensi, Kesehatan Kerja, Sikap Kerja, Kepemimpinan Dan Kondisi Tempat Kerja Terhadap Efektivitas Kerja Pegawai Kantor Lurah Tanjung Enim Selatan Kabupaten Muara Enim - Nursamsi, Nursamsi; Abdul Hamid; Delvina Yulanda (Journal of Law, Social Science, and Management Review, 2025)
This study aims to determine and analyze the influence of competence, occupational health, work attitude, leadership, and workplace conditions, individually and collectively, on the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial tests, simultaneous tests, and coefficients of determination. The analysis results showed that competence significantly influenced the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency. Occupational health significantly influenced the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency. Work attitude did not significantly influence the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency. Leadership significantly influenced the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency. Workplace conditions significantly influenced the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency. Competence, occupational health, work attitude, leadership, and workplace conditions have a significant joint influence on the work effectiveness of employees at the South Tanjung Enim Village Office, Muara Enim Regency.